Synergistic effects of α-Fe2O3 nanoparticles and Fe-doping on gas-sensing performance of NiO nanowires and interface mechanism. (6th September 2021) - Niu, J Y; Wang, L; Hong, B; Xu, J C; Han, Y B; Jin, H X; Zeng, Y X; Peng, X L; Ge, H L; Wang, X Q
Abstract: High surface area nickel oxide nanowires (NiO NWs), Fe-doped NiO NWs and α -Fe2 O3 /Fe-doped NiO NWs were synthesized with nanocasting pathway, and then the morphology, microstructure and components of all samples were characterized with XRD, TEM, EDS, UV–vis spectra and nitrogen adsorption–desorption isotherms. Owing to the uniform mesoporous template, all samples with the same diameter exhibit the similar mesoporous-structures. The loaded α -Fe2 O3 nanoparticles should exist in mesoporous channels between Fe-doped NiO NWs to form heterogeneous contact at the interface of n-type α -Fe2 O3 nanoparticles and p-type NiO NWs. The gas-sensing results indicate that Fe-dopant and α -Fe2 O3 -loading both improve the gas-sensing performance of NiO NWs sensors. α -Fe2 O3 /Fe-doped NiO NWs sensors presented the highest response to 100 ppm ethanol gas (55.264) compared with Fe-doped NiO NWs (24.617) and NiO NWs sensors (3.189). The donor Fe-dopant increases the ground state resistance and the absorbed oxygen content in air. α -Fe2 O3 nanoparticles in electron depletion region result in the increasing resistance in ethanol gas and decreasing resistance in air. In this way, α -Fe2 O3 /Fe-doped NiO NWs sensor presents the excellent gas-sensing performance due to the formation of heterogeneous contact at the interface.